Spatial database of planted forests in East Asia - Abbasi, Akane O.; Tang, Xiaolu; Harris, Nancy L.; Goldman, Elizabeth D.; Gamarra, Javier G. P.; Herold, Martin; Kim, Hyun Seok; Luo, Weixue; Silva, Carlos Alberto; Tchebakova, Nadezhda M.; Mitra, Ankita; Finegold, Yelena; et al. (Nature Portfolio, 2023)
Planted forests are critical to climate change mitigation and constitute a major supplier of timber/non-timber products and other ecosystem services. Globally, approximately 36% of planted forest area is located in East Asia. However, reliable records of the geographic distribution and tree species composition of these planted forests remain very limited. Here, based on extensive in situ and remote sensing data, as well as an ensemble modeling approach, we present the first spatial database of planted forests for East Asia, which consists of maps of the geographic distribution of planted forests and associated dominant tree genera. Of the predicted planted forest areas in East Asia (948,863 km2), China contributed 87%, most of which is located in the lowland tropical/subtropical regions, and Sichuan Basin. With 95% accuracy and an F1 score of 0.77, our spatially-continuous maps of planted forests enable accurate quantification of the role of planted forests in climate change mitigation. Our findings inform effective decision-making in forest conservation, management, and global restoration projects.